Analytical Tools for the Diagnostics and the Formation of a Management Team as an Element of the Organization Development Technique - L. A. Gorshkova; V. A. Poplavskaya (Учёт. Анализ. Аудит)
The purpose of the current research is to work out the tools for the diagnostics and the formation of a management team as the subject of organization development within the developed by the authors complicated cyclical technique of adjusting the condition of the external environment to the potential of the controlled object, the elements of the controlled subject and the life cycle stages of the organization. The following analytical methods are used in the research: points and marks method, expert method, target method, commission and conference method, business games, comparison method, test questions, questionnaire, suggestion box, method of active sociological tested analysis and control. The authors demonstrate and justify the necessity of expertise, knowledge and skills for the management team, which in turn should correspond to such types as “enthusiasts” (infancy), “achievers” (growth), “defenders” (maturity), “bureaucrats” (decline) at different life cycle stages of the organization. The tools suggested by the authors are intended to be used at large industrial enterprises. The results obtained by the authors can be taken as the basis for further both theoretical and applied research in the field of analysis of management system of modern economic entities.